Andesipolis, a puzzling new genus of cyclostome Braconidae (Hymenoptera) from the Chilean Andes, with descriptions of three new species - Whitfield, James B.; Choi, Won-Young; Suh, Kyong-In (Zootaxa, 2004)
A new genus of braconid wasp, Andesipolis Whitfield & Choi, n. g., is described from the Andean region of Chile. It clearly belongs to the cyclostome lineage of Braconidae but otherwise is difficult to assign definitively to tribe or subfamily, as it has some morphological features typical of Rhysipolini, others typical of Rhyssalini, and a few unique features. Three species, A. whartoni n. sp., A. masoni, n. sp. and A. framea n. sp. are described to represent the range of morphological variation encompassed by the new generic concept; other species are known to exist in collections but await a full-scale revision of this locally abundant genus.